Literature Review on the Integration of Epidemiology and Environmental Health in Disease Risk Mitigation - Ellxi Lidya Louiz Kandou; Sabrina Tertia Rucita Aramintana (PT Bukuloka Literasi Bangsa, 2025)
ABSTRACT This study aims to analyze the integration of epidemiology and environmental health as a strategic framework for mitigating disease risks in both communicable and non-communicable contexts. Using a qualitative descriptive research design through a systematic literature review, this article synthesizes academic journals, official reports, and relevant books published between 2014 and 2025. Data collection involved structured literature searches and document analysis, while data interpretation followed inductive thematic analysis through stages of coding, categorization, and synthesis. The findings reveal that integrating epidemiological methods with environmental health initiatives—such as Wastewater-Based Epidemiology (WBE), Environmental Public Health Tracking (EPHT), and Big Data–Geospatial Analytics—significantly improves disease surveillance, early detection, and health policy effectiveness. Moreover, the integration enhances the precision of environmental risk assessment and fosters adaptive, evidence-based decision-making. Despite its transformative potential, challenges persist, including fragmented data systems, limited interdisciplinary collaboration, and unequal access to environmental information. The study concludes that this integration strengthens theoretical models like the One Health and exposome paradigms while contributing to practical innovations in sustainable and equitable public health governance. These findings provide critical insights for policymakers, researchers, and practitioners seeking to design resilient health systems responsive to modern environmental and epidemiological threats. Keywords: epidemiology, environmental health, disease risk mitigation, One Health, public health integration